GLOBAL SECURITY INITIATIVE AS AN EFFORT TO MAINTAIN REGIONAL PEACE - Widya Setiabudi Sumadinata (SEAN Institute, 2023)
This research aims to explore global security initiatives as an effort to maintain peace in the region. In the context of increasingly complex and rapidly changing global dynamics, security challenges are becoming increasingly complex and require a more holistic and integrated response from various global actors. Based on literature review and analysis of secondary data, this study identified several principles such as shared, comprehensive, cooperative and sustainable security vision, respecting the sovereignty and territorial integrity of all countries, complying with the goals and principles of the UN Charter, taking the legitimate security issues of all countries seriously. , resolve differences and disputes peacefully between countries through dialogue and consultation and maintain security in traditional and non-traditional spheres. This research finds that global security initiatives can make a significant contribution in maintaining regional peace. However, this research also shows that the implementation of effective global security initiatives requires strong political support, intensive cooperation from various global actors, and increased institutional capacity in overcoming global security challenges. Therefore, this study concludes that global security initiatives can be an effective alternative to maintain peace in the region, however, they need to receive more serious attention from global policy makers in efforts to build sustainable and stable peace in the region